(untitled) (Research, Society and Development, 2020)
The nutritional status of a child plays a fundamental role in progressive growth and helps them develop social and psychomotor skills. The objective of this study was to characterize the nutritional status of students participating in an extension project of a community university. The sample included 80 children, between 5 and 6 years of age and enrolled in the first year of elementary school in public schools. To assess nutritional status, weight and height, triceps skinfold and subscapular skinfold data were collected, in addition to age and gender. Body mass index for age (BMI/I) was used to classify nutritional status. It was found that 17.6% of the sample presented overweight, obesity and severe obesity rates. The study showed a higher frequency of obesity in female schoolchildren (p = 0.034). There is a prevalence of eutrophic patterns in the students evaluated, but the overweight pattern was assessed in 11.3%, obesity in 5% and severe obesity in 1.3%. With the results found, the implementation of educational programs with the objective of raising awareness among the school community about the problem of obesity is important to create appropriate solutions for different populations, in favor of the eradication of obesity in children.